Pluralismo constitucional y los principios como metacriterios constitucionales - Solano Solano, Eduardo (2026)
The interaction between the international courts on human rights and the Constitutional Courts of each State has generated new aspects of interpretation of constitutional law. In this scenario, the vision of a constitutional pluralism is born that seeks to encompass the form of the new interaction of the jurisprudence of both bodies, but instead of doing it in a hierarchical way, a network model emerges in which both instances feed and they complement each other.